Evaluation of the influence of protein p53 in penile carcinoma - Gil, Antonio O.; Pompeo, Antonio C.L.; Sarkis, Álvaro S.; Matsuo, Mario; Da Motta, Tania H.B.V.; Arap, Sami (My University, 2002)
Introduction: The expression of protein p53 and its influence in the biological behavior of penile epidermoid carcinoma (PEC) were studied according to its effect on the following parameters: histologic staging, clinical and pathologic staging, and prognostic factors, such as survival curve and risk of death due to the tumor. Material and Methods: We studied 55 patients with PEC who underwent surgical treatment from 1979 to 1995. Protein p53 was studied by immunohistochemical analysis (clone DO-7-DAKO A/S, Denmark) in the most representative surgical specimens of the primary tumor and their metastasis. The intensity of p53 expression was determined by the number of tumor cell nuclei stained in the tumor and was classified into four groups: group 1 - up to 25%; group 2 - 26 to 50%; group 3 - 51 to 75% and group 4 - more than 75% stained nuclei. The relationship between the p53 expression in the tumor cells and the studied parameters was analyzed. Results: Rising rates of p53 expression correlate with low degrees of cell differentiation (p = 0.053). Twelve patients died due to the tumor during this study. Our data have shown that higher p53 expression in the tumor correlates with worse prognosis (p = 0.025). There was no significant correlation between the presence of p53 and the clinical or pathological stage of the tumor. Conclusion: Our data show that there is significant p53 expression in the PEC. The higher p53 expression, the worse the patient prognosis and the greater is the tumor biological agressiveness. The tumor becomes more aggressive in accordance with the increase in protein intensity in the tumor cell nuclei.
Keywords: Carcinoma; Penis; Prognosis; Protein p53; Tumor